High-strength plasticity copper-containing martensitic precipitation hardening stainless steel and method for manufacturing the same

CN117778896BActive Publication Date: 2026-10-13NORTHEASTERN UNIV CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311803414.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-25
Publication Date
2026-10-13
Estimated Expiration
2043-12-25

AI Technical Summary

Technical Problem

随着时效温度升高,该钢的强度与塑、韧性呈现此消彼长的关系,在450℃~500℃的峰值时效状态下,钢的抗拉强度能够达到1300MPa级别,延伸率保持在16%左右;随着时效温度的升高,过时效组织中会生成一定体积分数的逆变奥氏体,使得塑、韧性满足某些特殊的构件要求,但是抗拉强度会降低200MPa左右

Benefits of technology

[0028]本发明通过成分优化和工艺设计,获得了一种新型的Q&AP型马氏体沉淀硬化不锈钢15-5PH(C,N),奥氏体化后经不完全淬火得到低碳(氮)马氏体+残留奥氏体的双相组织,然后通过时效-配分处理使强化相析出的同时迫使马氏体中的过饱和的碳(氮)元素向奥氏体中富集,最后冷却到室温获得沉淀硬化马氏体+富碳(氮)奥氏体的双相组织。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117778896B_ABST
    Figure CN117778896B_ABST
Patent Text Reader

Abstract

The application discloses a high-strength and high-plasticity copper-containing martensite precipitation hardening stainless steel and a preparation method thereof, and belongs to the technical field of special steel smelting and processing. The steel comprises the following components in percentage by mass: C: 0.04-0.20%, Si: 0.2-0.6%, Mn: 0.2-1.0%, P: less than or equal to 0.02%, S: less than or equal to 0.01%, Cr: 12.7-15.7%, Ni: 3.8-5.2%, Mo: 0.6-1.0%, Cu: 2.6-3.4%, Al: less than or equal to 0.04%, Ti: less than or equal to 0.02%, N: 0.01-0.12%, and the balance of Fe. The preparation method comprises the following steps: preparing materials according to the component proportion; smelting in a vacuum melting furnace and casting a steel ingot; heating rolling or forging; high-temperature heating treatment, quenching and cooling; and aging and distribution heat treatment. The application introduces dispersedly distributed residual austenite in the microstructure in the peak hardening state to improve the strength, plasticity, strength and elongation of the steel through component design and heat treatment process adjustment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of special steel smelting and processing technology, specifically relating to a high-strength, ductile copper-containing martensitic precipitation hardening stainless steel and its preparation method. Background Technology

[0002] High-strength stainless steel is widely used in equipment manufacturing fields vital to national economy and people's livelihood, such as aerospace, marine engineering, and energy. Based on the performance requirements of good corrosion resistance and excellent strength and toughness matching, based on the composition of martensitic chromium-nickel stainless steel, alloying elements required to form various strengthening phases are added according to stoichiometric ratios, and a series of martensitic precipitation hardening stainless steels represented by 15-5PH steel, PH13-8Mo steel, and Custom465 steel have been developed.

[0003] As one of the earliest developed precipitation-hardening stainless steels, 15-5PH steel utilizes the precipitation strengthening effect of the ε-Cu phase to improve strength, thus offering low cost and wide application. This type of steel is typically austenitized and its elements dissolved at 1020℃~1060℃, then rapidly cooled to room temperature before aging at 480℃~620℃. With increasing aging temperature, the steel's strength, plasticity, and toughness exhibit an inverse relationship. At the peak aging state of 450℃~500℃, the steel's tensile strength can reach 1300MPa, while the elongation remains around 16%. As the aging temperature increases, a certain volume fraction of inverted austenite is generated in the over-aged microstructure, allowing the plasticity and toughness to meet the requirements of certain special components, but the tensile strength decreases by approximately 200MPa.

[0004] The overall strength and ductility of 15-5PH steel are not high, which reduces the expected service safety. In particular, insufficient strength has become the main bottleneck limiting its application range. Under more stringent service conditions, it is necessary to choose steel grades with higher strength levels and alloy element contents, such as PH13-8Mo and Custom465, resulting in a huge waste of resources. Therefore, improving the strength, ductility, and toughness of 15-5PH steel still has important engineering significance. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide an alloy composition for Cu-containing martensitic precipitation-hardening stainless steel 15-5PH(C,N) and a quenching and aging plus partitioning (Q&AP) heat treatment process. This invention, through compositional design and adjustment of the heat treatment process, introduces dispersed retained austenite into the microstructure at the peak hardening state to enhance the steel's strength and ductility, significantly improving the strength and elongation of the novel precipitation-hardening martensitic stainless steel.

[0006] A high-strength, ductile copper-containing martensitic precipitation-hardening stainless steel has the following chemical composition by mass fraction: C: 0.04–0.20%, Si: 0.2–0.6%, Mn: 0.2–1.0%, P≤0.02%, S≤0.01%, Cr: 12.7–15.7%, Ni: 3.8–5.2%, Mo: 0.6–1.0%, Cu: 2.6–3.4%, Al≤0.04%, Ti≤0.02%, N: 0.01–0.12%, with the balance being Fe.

[0007] A method for preparing high-strength, ductile copper-containing martensitic precipitation-hardening stainless steel specifically includes the following steps:

[0008] (1) Prepare materials according to the alloy composition ratio;

[0009] (2) Smelting in a vacuum melting furnace and casting steel ingots;

[0010] (3) Heating and rolling or forging;

[0011] (4) High temperature heating treatment and quenching cooling: After heating the workpiece in the furnace, keep it at the temperature, and then place it in air or oil to cool to room temperature, or immediately cool it down with ice water and keep it at the temperature after cooling to room temperature.

[0012] (5) Aging and heat treatment: The quenched and cooled workpiece is placed in a tempering furnace and heated with the furnace for aging treatment. After reaching the set temperature, it is air-cooled.

[0013] in:

[0014] In step (1), the element burn-off rate is estimated according to the equipment parameters during the alloy composition process, and the amount added is calculated according to the mass percentage of the alloy elements.

[0015] In step (2), the smelting process is carried out in a vacuum melting furnace, and high vacuum melting is used throughout the process, with the vacuum degree reaching below 0.1 Pa.

[0016] In step (2), the refining temperature during the smelting process is 1550-1650℃, the smelting time is not less than 30 minutes and not more than 60 minutes, and the stirring time is not less than 10 minutes and not more than 20 minutes.

[0017] In step (3), heating is carried out in air during the heating rolling or forging process. The heating method is furnace heating, and the heating rate is 100-180℃ / h.

[0018] In step (3), the specific process of heating and rolling or forging is as follows: the billet is heated to 1000-1300℃, held for 10-20h and then rolled or forged; the deformation of rolling or forging is not less than 50%, and it is conventionally rolled into the plate or bar required for the product.

[0019] In step (4), the high-temperature heating specifically involves heating in air or a reducing protective atmosphere at a rate of 100–180°C / h to heat the steel to 950–1050°C and hold it at that temperature for 30–120 minutes.

[0020] In step (4), when ice water is used to cool and keep the temperature during the quenching process, the holding time is 1 hour.

[0021] In step (5), the aging treatment temperature is 480-520℃, the time to reach the temperature is 4-10 hours, and then it is air-cooled to room temperature.

[0022] The workpiece is cooled to room temperature during the quenching and cooling stage. The mechanical properties of the high-strength and ductile copper-containing martensitic precipitation hardening stainless steel are as follows: impact energy ≥60J, yield strength ≥1200MPa, tensile strength ≥1500MPa, elongation ≥20%, and reduction of area ≥60%.

[0023] After the workpiece is cooled to room temperature during the quenching and cooling stage, it is immediately cooled with ice water and kept at that temperature. The mechanical properties of the high-strength, ductile copper-containing martensitic precipitation hardening stainless steel are as follows: impact energy ≥40J, yield strength ≥1300MPa, tensile strength ≥1500MPa, elongation ≥16%, and reduction of area ≥50%.

[0024] The key technical point of this invention is:

[0025] The steel composition of this invention is designed to have a dual-phase structure of low-carbon (nitrogen) martensite plus retained austenite at room temperature after quenching. The quenching cooling termination temperature should be 0℃~25℃. The quenching termination temperature can effectively affect the retained austenite content. A reasonable yield strength level can be obtained by controlling the quenching termination temperature.

[0026] The aging treatment temperature of the present invention is 480-520℃, and the holding time is 4-10h. This temperature and time ratio enables the room temperature after treatment to obtain a dual-phase structure of martensite + carbon (nitrogen) rich austenite, while the Cu-rich precipitate reaches the peak aging state, which further improves the strength without affecting the plasticity and toughness.

[0027] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0028] This invention obtains a novel Q&AP type martensitic precipitation hardening stainless steel 15-5PH(C,N) through composition optimization and process design. After austenitization, incomplete quenching is performed to obtain a duplex structure of low carbon (nitrogen) martensite + retained austenite. Then, aging-partitioning treatment is performed to precipitate the strengthening phase while forcing the supersaturated carbon (nitrogen) elements in the martensite to enrich into the austenite. Finally, cooling to room temperature yields a duplex structure of precipitation hardening martensite + carbon (nitrogen) rich austenite.

[0029] The experimental steel, after aging and fractionation treatment at 480–520℃, achieved an optimal strength-ductility ratio. At this temperature, the retained austenite content in the microstructure was approximately 20%, resulting in a yield strength of 1200 MPa, a tensile strength of 1500 MPa, an elongation exceeding 22%, a reduction of area of ​​approximately 65%, and an impact energy of 60 J. Compared to commercially available 15-5PH, while maintaining comparable impact and fracture toughness, the tensile strength increased by 200 MPa, and the elongation increased by over 5%. Furthermore, through compositional fine-tuning and process optimization, adjusting the retained austenite content in the Q&AP microstructure to between 15% and 18% achieved a yield strength of 1350 MPa, a tensile strength of 1500 MPa, an elongation of approximately 18%, a reduction of area of ​​approximately 50%, and an impact energy of 40 J. Its mechanical properties met the standard of PH13-8Mo, significantly reducing resource costs. Attached Figure Description

[0030] Figure 1 Microstructure of the copper-containing martensitic precipitation hardening stainless steel prepared in Example 1 of this invention;

[0031] Figure 2 Stress-strain curves of copper-containing martensitic precipitation hardening stainless steel prepared in Examples 1-3 of this invention;

[0032] Figure 3 XRD diffraction patterns of copper-containing martensitic precipitation hardening stainless steel prepared in Examples 1-3 of this invention. Detailed Implementation

[0033] Example 1

[0034] A method for preparing high-strength, ductile copper-containing martensitic precipitation-hardening stainless steel specifically includes the following steps:

[0035] (1) Prepare materials according to the alloy composition ratio. The chemical composition is as follows (by mass fraction): C: 0.06%, Si: 0.4%, Mn: 0.4%, Cr: 13.5%, Ni: 5.2%, Mo: 0.8%, Cu: 3.3%, N: 0.08%, with the balance being Fe;

[0036] (2) Experimental steel was smelted using a 50kg vacuum induction furnace. The entire smelting process was carried out under high vacuum, with the vacuum level reaching below 0.1Pa. The refining temperature during the smelting process was 1600℃, the smelting time was 30min, and the stirring time was 10min.

[0037] (3) The molten billet is heated in an air furnace. The heating method is furnace heating with a heating rate of 100℃ / h. The billet is heated to 1100℃ and held for 15h before being taken out of the furnace and rolled. The deformation is 50%, and it is conventionally rolled into a 25mm thick plate. Several 70mm×40mm×25mm block samples are cut from the hot-rolled plate for Q&AP heat treatment.

[0038] (4) Place the block sample in an air furnace and heat it to 1000°C at a heating rate of 150°C / h. After holding it at that temperature for 30 minutes, remove it from the furnace, air cool it to room temperature, and then immediately cool it down to 0°C with ice water and hold it at that temperature for 1 hour.

[0039] (5) Place it in a tempering furnace and heat it to 480°C for aging treatment. After 8 hours of aging, place it in the air to cool to room temperature.

[0040] The microstructure of the prepared high-strength, high-ductility copper-containing martensitic precipitation-hardening stainless steel is shown in the figure below. Figure 1 As shown.

[0041] Example 2

[0042] A high-strength, ductile copper-containing martensitic precipitation-hardening stainless steel is produced using the same smelting process and final chemical composition of the smelted billet as in Example 1. The rolling, high-temperature heating, and quenching processes are also the same as in Example 1. The heat treatment process is as follows:

[0043] (1) Place the block sample in an air furnace and heat it to 1000°C at a heating rate of 150°C / h. After holding it at that temperature for 30 minutes, remove it from the furnace and air cool it to room temperature of 25°C.

[0044] (2) Place it in a tempering furnace and heat it to 480°C for aging treatment. After 8 hours of aging, place it in the air to cool to room temperature.

[0045] Example 3

[0046] A high-strength, ductile copper-containing martensitic precipitation-hardening stainless steel, the smelting process and the final chemical composition of the smelted billet, by mass fraction percentage, are as follows: C: 0.08%, Si: 0.4%, Mn: 0.4%, Cr: 14.5%, Ni: 4.6%, Mo: 0.8%, Cu: 3.0%, N: 0.08%, with the balance being Fe; the rolling, high-temperature heating treatment, and quenching cooling processes are the same as in Example 1, and the heat treatment process is as follows:

[0047] (1) Place the block sample in an air furnace and heat it to 1000℃ at a heating rate of 150℃ / h. After holding it at that temperature for 30 minutes, remove it from the furnace, air cool it to room temperature, and then immediately cool it down to 0℃ with ice water and hold it at that temperature for 1 hour.

[0048] (2) Place it in a tempering furnace and heat it to 500°C for aging treatment. Wait 6 hours until it reaches the set temperature, then place it in the air to cool to room temperature.

[0049] Example 4

[0050] A high-strength, ductile copper-containing martensitic precipitation-hardening stainless steel is produced using the same smelting process and final chemical composition of the smelted billet as in Example 3. The rolling, high-temperature heating, and quenching processes are also the same as in Example 1. The heat treatment process is as follows:

[0051] (1) Place the block sample in an air furnace and heat it to 1000°C at a heating rate of 150°C / h. After holding it at that temperature for 30 minutes, remove it from the furnace and air cool it to room temperature of 25°C.

[0052] (2) Place it in a tempering furnace and heat it to 500°C for aging treatment. After 8 hours of aging, place it in the air to cool to room temperature.

[0053] Example 5

[0054] A high-strength, ductile copper-containing martensitic precipitation-hardening stainless steel, the smelting process and the final chemical composition of the smelted billet, by mass fraction percentage, are: C: 0.06%, Si: 0.4%, Mn: 0.8%, Cr: 15.5%, Ni: 3.2%, Mo: 0.6%, Cu: 3.4%, N: 0.10%, with the balance being Fe; the rolling, high-temperature heating treatment, and quenching cooling processes are the same as in Example 1, and the heat treatment process is as follows:

[0055] (1) Place the block sample in an air furnace and heat it to 1000℃ at a heating rate of 150℃ / h. After holding it at that temperature for 30 minutes, remove it from the furnace, air cool it to room temperature, and then immediately cool it down to 0℃ with ice water and hold it at that temperature for 1 hour.

[0056] (2) Place it in a tempering furnace and heat it to 480°C for aging treatment. Wait 10 hours until it reaches the set temperature, then place it in the air to cool to room temperature.

[0057] Example 6

[0058] A high-strength, ductile copper-containing martensitic precipitation-hardening stainless steel is produced using the same smelting process and final chemical composition of the smelted billet as in Example 5. The rolling, high-temperature heating, and quenching processes are also the same as in Example 1. The heat treatment process is as follows:

[0059] (1) Place the block sample in an air furnace and heat it to 1000°C at a heating rate of 150°C / h. After holding it at that temperature for 30 minutes, remove it from the furnace and air cool it to room temperature of 25°C.

[0060] (2) Place it in a tempering furnace and heat it to 480°C for aging treatment. Wait 10 hours until it reaches the set temperature, then place it in the air to cool to room temperature.

[0061] Example 7

[0062] A high-strength, ductile copper-containing martensitic precipitation-hardening stainless steel, the smelting process and the final chemical composition of the smelted billet, by mass fraction percentage, are as follows: C: 0.14%, Si: 0.4%, Mn: 0.4%, Cr: 14.4%, Ni: 4.2%, Mo: 0.6%, Cu: 3.6%, N: 0.01%, with the balance being Fe; the rolling, high-temperature heating treatment, and quenching cooling processes are the same as in Example 1, and the heat treatment process is as follows:

[0063] (1) Place the block sample in an air furnace and heat it to 1000℃ at a heating rate of 150℃ / h. After holding it at that temperature for 30 minutes, remove it from the furnace, air cool it to room temperature, and then immediately cool it down to 0℃ with ice water and hold it at that temperature for 1 hour.

[0064] (2) Place it in a tempering furnace and heat it to 480°C for aging treatment. After 6 hours of aging, place it in the air to cool to room temperature.

[0065] Example 8

[0066] A high-strength, ductile copper-containing martensitic precipitation-hardening stainless steel has the same smelting process and final chemical composition of the smelted billet as in Example 7. The rolling, high-temperature heating treatment, and quenching cooling processes are also the same as in Example 1. The heat treatment process is as follows:

[0067] (1) Place the block sample in an air furnace and heat it to 1000°C at a heating rate of 150°C / h. After holding it at that temperature for 30 minutes, remove it from the furnace and air cool it to room temperature of 25°C.

[0068] (2) Place it in a tempering furnace and heat it to 480°C for aging treatment. After 6 hours of aging, place it in the air to cool to room temperature.

[0069] All examples were tested using a JBW-500 impact testing machine, with U-notch specimens measuring 10mm × 10mm × 55mm. Tensile tests were performed using a Shimadzu AG-X Plus 100KN tensile testing machine, with specimens 25mm in length and 5mm in diameter. The tensile rate was 2mm / min, and an extensometer with a 25mm range was used to measure the strain before reaching the maximum load. The average of three sets of measurements was taken for both tests. The stress-strain curves of the copper-containing martensitic precipitation-hardening stainless steel prepared in Examples 1-3 are shown below. Figure 2 As shown, the XRD diffraction pattern is as follows: Figure 3 As shown.

[0070] The results of the measurement and analysis conducted on the above embodiments are shown in the table below:

[0071]

[0072] In the above schemes, comparing Examples 1 and 2, it can be seen that lowering the quenching stop temperature after austenitization (cooling to room temperature followed by ice water treatment) reduces the austenite content in the quenched microstructure, increasing the yield strength, but also leading to a decrease in elongation and impact absorption energy. Under the synergistic effect of the matrix structure and precipitated phases, the present invention achieves the optimal mechanical property ratio after austenitization at 1000℃ for 30 min, air cooling to 25℃, and then aging at 480℃ for 8 h, with an impact absorption energy of 63 J, a yield strength of 1235 MPa, a tensile strength of 1538 MPa, an elongation of 22.7%, and a reduction of area of ​​60%. Cooling to room temperature after austenitization followed by ice water treatment can achieve even higher yield strength, but at the cost of some plasticity and toughness. Depending on the different performance characteristics required for the product, the quenching stop temperature can be appropriately changed to adjust the yield strength, and the aging temperature and time can be changed to obtain different strength and plasticity properties.

[0073] In the above schemes, by comparing Examples 1, 3, 5 and 7, it can be seen that the content of C, N, Cr, Ni, Mn and Mo elements in the steel composition can be adjusted in a coordinated manner to adapt to different service environments and cost requirements, and the result has little impact on the microstructure and mechanical properties after heat treatment.

Claims

1. A method for preparing high-strength, ductile copper-containing martensitic precipitation-hardening stainless steel, characterized in that, Specifically, the following steps are included: (1) Prepare materials according to the alloy composition ratio; (2) Smelting in a vacuum melting furnace and casting steel ingots; (3) Heating and rolling or forging; (4) High temperature heating treatment and quenching cooling: After heating the workpiece in the furnace, keep it at the temperature, and then place it in air or oil to cool to room temperature, or immediately cool it down with ice water and keep it at the temperature after cooling to room temperature; (5) Aging and heat treatment: The quenched and cooled workpiece is placed in a tempering furnace and heated in the furnace for aging treatment. After reaching the set temperature, it is air-cooled. The chemical composition of the alloy is as follows (by mass fraction): C: 0.08~0.20%, Si: 0.2~0.6%, Mn: 0.2~1.0%, P≤0.02%, S≤0.01%, Cr: 12.7~15.7%, Ni: 3.8~5.2%, Mo: 0.6~1.0%, Cu: 2.6~3.4%, Al≤0.04%, Ti≤0.02%, N: 0.01~0.12%, with the balance being Fe. In step (3), the heating process is carried out in air during the heating rolling or forging process. The heating method is furnace heating, and the heating rate is 100~180℃ / h. The specific process of heating rolling or forging is as follows: the billet is heated to 1000~1300℃, held for 10~20 h, and then rolled or forged. The deformation of the rolling or forging is not less than 50%, and it is conventionally rolled into the plate or bar required for the product. In step (4), when the workpiece is heated in the furnace, the heating rate is 100~180℃ / h; In step (4), when cold water is used to cool down and keep the temperature during the quenching process, the holding time is 1 hour. In step (4), the high-temperature heating specifically involves heating the steel in air or a reducing protective atmosphere to 950~1050℃ and holding it for 30~120 min. In step (5), the aging and distribution treatment temperature is 480~520℃, the time to reach the temperature is 4~10 h, and then air-cooled to room temperature.

2. The method for preparing a high-strength, ductile copper-containing martensitic precipitation-hardening stainless steel according to claim 1, characterized in that, In step (1), the element burn-off rate is estimated according to the equipment parameters during the alloy composition process, and the amount added is calculated according to the mass percentage of the alloy elements.

3. The method for preparing a high-strength, ductile copper-containing martensitic precipitation-hardening stainless steel according to claim 1, characterized in that, In step (2), the smelting process is carried out in a vacuum melting furnace, and the entire process is carried out in a high vacuum melting process with a vacuum degree of less than 0.1 Pa. The refining temperature during the melting process is 1550~1650℃, the melting time is not less than 30 min and not more than 60 min, and the stirring time is not less than 10 min and not more than 20 min.

4. The method for preparing a high-strength, ductile copper-containing martensitic precipitation-hardening stainless steel according to claim 1, characterized in that, The workpiece is cooled to room temperature during the quenching and cooling stage. The mechanical properties of the high-strength and ductile copper-containing martensitic precipitation hardening stainless steel are as follows: impact energy ≥60 J, yield strength ≥1200 MPa, tensile strength ≥1500 MPa, elongation ≥20%, and reduction of area ≥60%.

5. The method for preparing a high-strength, ductile copper-containing martensitic precipitation-hardening stainless steel according to claim 1, characterized in that, After the workpiece is cooled to room temperature during the quenching and cooling stage, it is immediately cooled with ice water and kept at that temperature. The mechanical properties of the resulting high-strength, ductile copper-containing martensitic precipitation hardening stainless steel are as follows: impact energy ≥40 J, yield strength ≥1300 MPa, tensile strength ≥1500 MPa, elongation ≥16%, and reduction of area ≥50%.

Citation Information

Patent Citations

  • High-strength, high-toughness and high-plasticity martensitic stainless steel and preparation method thereof

    CN103614649A

  • High-strength martensitic stainless steel and method for making the same

    US5496421A